DAMPAK PUTUSAN PENGADILAN TERHADAP SANGSI PADA ANAK PELAKU PERUNDUNGAN DALAM INTENSITAS PERILAKU VERBAL ( SUATU TINJAUAN UNDANG- UNDANG NOMER 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK) - Heru Ismaya; Rika Jazilatul Kholidah (Verstek, 2026)
Bullying can be interpreted as a form of structured violence carried out with the aim of intimidating and maintaining dominance by a particular individual or group over a stronger entity. The court, as a legal institution, functions as an enforcement agency. Children are part of the younger generation and are a human resource that plays a strategic role in the future of the nation's ongoing struggle. The purpose of this study is to describe the deterrent effect of sanctions imposed on perpetrators of bullying in terms of the intensity of verbal behavior. The punishment for perpetrators of bullying according to Article 76 C of Law Number 35 of 2014 are as follows; "Everyone is prohibited from placing, allowing, committing, ordering, or participating in committing violence against children" (Law Number 35 of 2014). It means that what is meant by everyone is an individual or corporation, while the meaning of a child is someone who is not yet 18 years old. This article states that perpetrators of verbal bullying can be punished with a maximum prison of 3 years and 6 months and/or a maximum fine of IDR 72 million. Indeed, perpetrators of criminal acts of bullying must be punished to prevent repeat acts. However, on the other hand, the long-term effects on the future of children who bully need to be considered.